(untitled) (Global Journal of Medical Research, 2023)
Blood pressure (BP) during sleep is a risk factor for cardiovascular disease. Poor sleep quality leads to hypertension. Sleep quality decreases with media device use and increases with deep breathing. Our objective was to examine the acute effects of slow breathing and refraining from using media devices on cardiac autonomic function and blood pressure during sleep. Fifteen healthy male participants were randomly assigned to one of three conditions: (a) slow breathing (BT) condition (12 consecutive breaths of 4 s of inhalation through the nose, 4 s pause, and 8 s of exhalation, approximately 3 min per breath), (b) a BT condition (BT+Non-LED) in which slow breathing was performed and the use of light-emitting devices (LED; smartphones, tablets, computers, etc.) was prohibited 1 hr before bedtime, and (c) a control condition (CON) in which slow breathing was not performed, and the use of LED was permitted. Blood pressure was measured by oscillometric method at baseline and 2 and 4 o’clock at bedtime. Autonomic function was measured by heart rate variability for 24 hours.